Implementasi Sistem Tranduser pada Peringatan Dini Banjir Berbasis Telegram - Astuti, Widia Tri; Yacoub, Redi Ratiandi; Marpaung, Jannus (Universitas Harapan Medan, 2024)
Floods as natural disasters are occurrences that can happen at any time and often result in loss of life and significant material damage. This research focuses on developing a transducer system for river water level monitoring based on Long Range Wireless Communication Technology and Internet of Things (IoT). The aim is to provide early warnings regarding river water levels, enabling the community to be more vigilant and minimize potential damage in the event of rising water levels. The research methodology involves utilizing a multiturn potentiometer in conjunction with Nodemcu ESP8266 and LoRa SX1278 devices. The results of the transducer system testing in a relevant environment showed an average difference of 0.27 cm, while testing in actual river water or real-world conditions yielded an average difference of 0.61 cm. The LoRa SX1278 testing at distances of 20 meters and 40 meters demonstrated a Packet Delivery Ratio (PDR) of 100% and a packet loss of 0%, indicating successful data reception. However, at a distance of 60 meters, the PDR was 90%, with a 10% packet loss, and at 70 meters, the PDR dropped to 10%, with a packet loss of 90%. This system includes Telegram notifications to allow users to access information on water levels as an early warning